PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR SISWA PADA MATERI PEMBAGIAN DI KELAS III SD NEGERI 1 MATA IE KABUPATEN ACEH BESAR - Maya Fika Lora; Mislinawati; Linda Vitoria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Thisfstudy wasfmotivated byfthe lowflevel offunderstanding of third-grade elementary school students regarding division material due to a learning approach that was not in line with the cognitive development of students. The Realistic Mathematics Education (RME) is considered capable of bridging this gap through real contexts and meaningful activities. Thisistudy aimsato determineithe effectiof theiRealisticaMathematicsaEducation onathe learningaoutcomes of third-gradeastudents at Mata Ie 1 Public Elementary School on division material. This studyfuses afquantitative approachfwith afpre-experimental OnefGroup Pretest–PosttestfDesign on 18 students. Datafwere collectedfthrough essay tests before and after learning, then analyzediusing theiPaired Sampleit-Test assistediby IBM SPSS Ver 26. Thefresults offthe analysis showed aiSig. (2-tailed)ivalue of 0.000i< 0.05,iwhich means H0 isirejected and H0 isiaccepted. Thus, the RealisticiMathematicsiEducation has an effect on improving student learning outcomes, although it requires time management and reinforcement of the concept of subtraction.